Renin–angiotensin system inhibition and risk of infection and mortality in COVID‐19: a systematic review and meta‐analysis. Issue 12 (16th November 2020) - Koshy, Anoop N.; Murphy, Alexandra C.; Farouque, Omar; Ramchand, Jay; Burrell, Louise M.; Yudi, Matias B.
Abstract: Background: Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), the causative agent of COVID‐19, enters human cells by binding of its viral protein to the aminopeptidase angiotensin‐converting enzyme 2 (ACE2). This has led to speculation whether treatment with renin–angiotensin system (RAS) inhibitors was associated with an increased likelihood of a positive test for COVID‐19 and risk of mortality. Aims: We performed a systematic review and meta‐analysis to investigate whether RAS inhibitors increased the likelihood of a positive test or death/severe illness in patients with COVID‐19. Methods: A systematic search of MEDLINE, PubMed and EMBASE was conducted for studies stratified by the use of angiotensin‐converting enzyme inhibitors (ACEI) or angiotensin receptor blockers (ARB). Pooled analysis was performed using a random‐effects model. Results: Seven trials of 73 122 patients were included. Overall, 16 624 (22.7%) patients had a positive COVID‐19 test and 7892 (10.8%) were on a RAS inhibitor. RAS inhibitors were not associated with higher likelihood of a positive COVID‐19 test result (odds ratio (OR) 0.97 (95% CI 0.97–1.05, P = 0.48) with low heterogeneity. This was comparable when stratifying by use of each medication class. The use of RAS inhibitors was also not associated with mortality or severe illness (OR 0.89, 95% CI 0.73–1.07, P = 0.21) with moderate heterogeneity. Conclusion: Use of ACEI or ARB was not associated with a heightened susceptibility for a positive diagnosis of COVID‐19. Furthermore, they were not associated with increased illness severity or mortality due to COVID‐19. Randomised controlled trials are needed to address definitively the potential benefits or harms of RAS inhibitors in patients with COVID‐19.